Асимптотичнi розв’язки лiнiйної системи з малим параметром при частинi похiдних - Ключник, I.Г. (Нелінійні коливання, 2010)
By using a transformation matrix, we reduce a system of differential equations with a small parameter at partial derivatives and a turning point to an integrable system of equations.